Influence of basalt fiber in ultra-high-performance concrete in hybrid mode: a comprehensive study on mechanical properties and microstructure - Sujitha Magdalene.P; Karthikeyan, B. (Revista de la Construcción. Journal of Construction, 2024)
The end, in view of the research, is to effectively utilize natural fiber (basalt) to reinstate the mechanical strength lost by the ultra-high-performance concrete (UHPC) matrix when the metallic steel fibers are quantitatively curtailed. Also, the river sand is fractionally ousted from the mixture, and manufactured sand is substituted. In addition to the preliminary constituents of UHPC, nano silica was adopted for the adequate packing of the matrix, which aids in strength-gaining reaction as well. To induce sustainability and implement waste utilization, two different proportions using M-Sand were made with 30% and 4% replacement levels, and for each proportion of M-Sand, five different mixes were made for varying fiber incorporation. Including the control mix made without any fiber, a total of 12 mixes were made. Among the fibrous mixes, two were metallic fibrous mixtures, and the rest were hybrid fibrous mixtures, and inter-comparisons were done accordingly. The metallic fibers were added in 1% and 2%, and natural fibers were incorporated in 1%, 2%, and 3% in volumetric fractions. From the trial mixes it was identified that the inclusion of Basalt fibers of more than 3% resulted in reduced workability, and so the addition of basalt fibers was restricted to 3%. The water-to-binder ratio of the UHPC matrix ranged between 0.15 and 0.17, depending upon the dosage of fibers. High range water reducer (HRWR) was mixed with water during casting, to develop the workability. The specimens were tested for compressive strength, split tensile strength, and impact energy resistance. It was identified that the annexation of 1% steel and 3% basalt fibers with 30% M-Sand was effective as they showed better compressive strength and impact resistance than the other combinations. Further Scanning Electron Microscopic (SEM) imaging and Thermogravimetric Analysis (TGA), which were conducted, also validated the inference from the experimental investigations.The end, in view of the research, is to effectively utilize natural fiber (basalt) to reinstate the mechanical strength lost by the ultra-high-performance concrete (UHPC) matrix when the metallic steel fibers are quantitatively curtailed. Also, the river sand is fractionally ousted from the mixture, and manufactured sand is substituted. In addition to the preliminary constituents of UHPC, nano silica was adopted for the adequate packing of the matrix, which aids in strength-gaining reaction as well. To induce sustainability and implement waste utilization, two different proportions using M-Sand were made with 30% and 4% replacement levels, and for each proportion of M-Sand, five different mixes were made for varying fiber incorporation. Including the control mix made without any fiber, a total of 12 mixes were made. Among the fibrous mixes, two were metallic fibrous mixtures, and the rest were hybrid fibrous mixtures, and inter-comparisons were done accordingly. The metallic fibers were added in 1% and 2%, and natural fibers were incorporated in 1%, 2%, and 3% in volumetric fractions. From the trial mixes it was identified that the inclusion of Basalt fibers of more than 3% resulted in reduced workability, and so the addition of basalt fibers was restricted to 3%. The water-to-binder ratio of the UHPC matrix ranged between 0.15 and 0.17, depending upon the dosage of fibers. High range water reducer (HRWR) was mixed with water during casting, to develop the workability. The specimens were tested for compressive strength, split tensile strength, and impact energy resistance. It was identified that the annexation of 1% steel and 3% basalt fibers with 30% M-Sand was effective as they showed better compressive strength and impact resistance than the other combinations. Further Scanning Electron Microscopic (SEM) imaging and Thermogravimetric Analysis (TGA), which were conducted, also validated the inference from the experimental investigations.